Ipung Novel by Prie Gs and Sang Alkemis Novel by Paulo Coelho (Comparative Literature Study) - Pana Pramulia; Nanda Saputra (Lakhomi Journal Scientific Journal of Culture, 2020)
Literary works in Indonesia, including novels, both in terms of ideas and content, are heavily influenced by works from abroad. This influence is caused by many things, for example Indonesian writers who idolize foreign writers, similarities in social situations and conditions, or even unplanned similarities because Indonesian writers unconsciously intensively read one of the works of foreign writers. This research attempts to compare the novel Ipung by Prie GS with the novel the Alchemist by Paulo Coelho. Comparisons are only limited to pouring out the ideas, genres, and motives contained in the two novels. This research is a descriptive qualitative research that describes a number of ideas, genres, and motives concerning the basic issues of creation, and the message can be expressed accuratel. Based on the research results, it was stated that the novel Sang Alkemis by Paulo Coelho influenced Prie GS novel Ipung, both in terms of ideas, genres, and motives.